2020
DOI: 10.1103/physrevaccelbeams.23.021304
|View full text |Cite
|
Sign up to set email alerts
|

Generating high quality ultrarelativistic electron beams using an evolving electron beam driver

Abstract: A new method of controllable injection to generate high quality electron bunches in the nonlinear blowout regime driven by electron beams is proposed and demonstrated using particle-in-cell simulations. Injection is facilitated by decreasing the wake phase velocity through varying the spot size of the drive beam and can be tuned through the Courant-Snyder (CS) parameters. Two regimes are examined. In the first, the spot size is focused according to the vacuum CS beta function, while in the second, it is focuse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…While PIC simulations can be used to determine the exact value of ψ min in the nonlinear blowout regime, ψ min can be well approximated by −1 when the maximum bubble radius is sufficiently large, i.e., r m 3. Under these conditions, sheath electrons that trace the bubble r b (ξ) travel near the speed of light, v z ∼ 1, with finite transverse momentum P ⊥ at the rear of the wake 16,20 . From the constant of motion for a plasma particle γ − P z = 1 + ψ 29 , it can be shown that 1…”
Section: The Plasma Wake Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…While PIC simulations can be used to determine the exact value of ψ min in the nonlinear blowout regime, ψ min can be well approximated by −1 when the maximum bubble radius is sufficiently large, i.e., r m 3. Under these conditions, sheath electrons that trace the bubble r b (ξ) travel near the speed of light, v z ∼ 1, with finite transverse momentum P ⊥ at the rear of the wake 16,20 . From the constant of motion for a plasma particle γ − P z = 1 + ψ 29 , it can be shown that 1…”
Section: The Plasma Wake Potentialmentioning
confidence: 99%
“…Recently, there have been many selfinjection schemes proposed to generate high quality electron beams with low energy spread σ γ and normalized emittance ǫ n . The most promising ideas typically involve decreasing the phase velocity γ φ of the plasma wake using either a plasma density down ramp [13][14][15][16][17] or an evolving driver [18][19][20] . In each of these instances, plasma electrons are injected at the very rear of the first bucket of the wake where they can then be accelerated over long periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of high quality electron beams [13][14][15][16][17] has been instrumental for these advances. Various techniques were developed to controllably inject electrons into a relativistic plasma wake, such as downramp trapping [18][19][20][21][22][23] and ionization injection [23][24][25][26][27].…”
mentioning
confidence: 99%
“…Various techniques were developed to controllably inject electrons into a relativistic plasma wake, such as downramp trapping [18][19][20][21][22][23] and ionization injection [23][24][25][26][27]. Recent work on plasma cathodes has opened the possibility of generating femtosecond duration electron beams with MeV energy spreads, peak currents as high as hundreds of kA [28,29] and normalized emittance n as low as 10's of nm [13,14,16,17,[30][31][32]. Besides having the potential to achieve unprecedented beam brightness, plasma cathodes can imprint multi-dimensional spatial structures onto the accelerated beams.…”
mentioning
confidence: 99%